The Influence of Work Motivation and Communication on Employee Performance at the Inspectorate of Central Tapanuli Regency - Pipi Ferida Panggabean; Kaharuddin Kaharuddin; Mhd. Shafwan Koto (Journal of Economics, Management and Accounting (JEMA), 2026)
This study aims to examine the effect of work motivation and communication on employee performance at the Inspectorate of Central Tapanuli Regency. This research uses a quantitative research method with a descriptive approach. The sample in this study consisted of 37 employees of the Inspectorate of Central Tapanuli Regency who were selected through questionnaire distribution. The results show that work motivation and communication have a positive and significant effect on employee performance. The coefficient of determination (R²) is 0.739, indicating that 73.9% of the variation in employee performance is explained by work motivation and communication, while the remaining 26.1% is influenced by other factors not examined in this study. The partial test (t-test) shows that work motivation has a significant effect on employee performance (t = 3.105; p < 0.05), and communication also has a significant effect on employee performance (t = 6.306; p < 0.05). Furthermore, the simultaneous test (F-test) indicates that work motivation and communication together have a positive and significant effect on employee performance (F = 48.077; p < 0.05). These findings suggest that improving employee motivation and strengthening organizational communication can enhance employee performance within the institution.